Numeric simulation on the performance of an undulating fin in the wake of a periodic oscillating plate - Zhang, Yong-Hua (2014)
A two-dimensional unsteady computational fluid dynamics (CFD) method using an unstructured, grid-based and unsteady Navier-Stokes solver with automatic adaptive re-meshing to compute the unsteady flow was adopted to study the hydrodynamic interaction between a periodic oscillating plate and a rigid undulating fin in tandem arrangement. The user-defined function (UDF) program was compiled to define the undulating and oscillating motion. First, the influence of the distance between the anterior oscillating plate and the posterior undulating fin on the non-dimensional drag coefficient of the fin was investigated. Ten different distances, D=0.2L, 0.4L, 0.6L, 0.8L, 1.0L, 1.2L, 1.4L, 1.6L, 1.8L and 2.0L, were considered. The performance of the fin for different distances (D) is different. Second, the plate oscillating angle (5.7o, 10 o, 20 o, 30 o, 40 o, 45 o, 50 o) and frequency (0.5 Hz, 1.0 Hz, 1.5 Hz, 2.0 Hz, 2.5 Hz, 3.0 Hz, 3.5 Hz, 4.0 Hz) effects on the non-dimensional drag coefficient of the fin were also implemented. The pressure distribution on the fin was computed and integrated to provide fin forces, which were decomposed into lift and thrust. Meanwhile, the flow field was demonstrated and analysed. Based on the flow structures, the reasons for different undulating performances were discussed. It shows that the results largely depend on the distance between the two objects. The plate oscillating angle and frequency also make a certain contribution to the performance of the posterior undulating fin. The results are similar to the interaction between two undulating objects in tandem arrangement and they may provide a physical insight into the understanding of fin interaction in fishes or bio-robotic underwater propulsors that are propelled by multi fins.